Α‐Blockers for uncomplicated ureteric stones: a clinical practice guideline. (31st August 2018) - Vermandere, Mieke; Kuijpers, Ton; Burgers, Jako S.; Kunnamo, Ilkka; van Lieshout, Jan; Wallace, Emma; Vlayen, Joan; Schoenfeld, Elizabeth; Siemieniuk, Reed A.; Trevena, Lyndal; Zhu, Xiaoye; Verermen, Francis; et al.
Abstract : Objective: To develop an evidence‐based recommendation concerning the use of α‐blockers for uncomplicated ureteric stones based on an up‐to‐date Cochrane review, as the role of medical expulsive therapy for uncomplicated ureteric stones remains controversial in the light of new contradictory trial evidence. Methods: We applied the Rapid Recommendations approach to guideline development, which represents an innovative approach by an international collaborative network of clinicians, researchers, methodologists and patient representatives seeking to rapidly respond to new, potentially practice‐changing evidence with recommendations developed according to standards for trustworthy guidelines. Results: The panel suggests the use of α‐blockers in addition to standard care over standard care alone in patients with uncomplicated ureteric stones (weak recommendation based on low‐quality evidence). The panel judged that the net benefit of α‐blockers was small and that there was considerable uncertainty about patients' values and preferences. This means that the panel expects that most patients would choose treatment with α‐blockers but that a substantial proportion would not. This recommendation applies to both patients in whom the presence of ureteric stones is confirmed by imaging, as well as patients in whom the diagnosis is made based on clinical grounds only. Conclusion: The Rapid Recommendations panel suggests the use of α‐blockers for patients with ureteric stones. Shared decision‐making is emphasised in making the final choice between the treatment options.